Biocompatible nitrogen-doped carbon dots: synthesis, characterization, and application. Issue 39 (9th September 2020) - Park, Yoonsang; Kim, Yujin; Chang, Heemin; Won, Sungyeon; Kim, Hyemin; Kwon, Woosung
Abstract : Nitrogen-doped carbon dots have emerged as a biocompatible functional carbon nanomaterial for a variety of biomedical applications such as optical imaging, photoacoustic imaging, drug delivery, photothermal therapy, and photodynamic therapy. Abstract : Carbon dots (CDs) are promising materials for biomedical applications owing to their unique properties, biocompatibility, and biodegradability. The current studies on CDs are focused on improving their functionality by modulating their electronic structure, which helps in controlling their chemical, optical, and electrical properties. Doping with heteroatoms is a typical approach for modulating the electronic structure of CDs. In particular, there has been considerable progress in nitrogen-doped CDs for improving their potential for various biomedical applications, including optical imaging, drug delivery, and light-mediated imaging/therapeutic applications such as photoacoustic imaging, photothermal therapy, and photodynamic therapy. In this review, the important features of nitrogen-doped CDs are discussed along with the recent studies on these materials and their prospects.